High Frequency Electric Field Levels: An Example of Determination of Measurement Uncertainty for Broadband Measurements - Vulević, Branislav; Grbić, Maja; Pavlović, Aleksandar (Proceedings, Electrical engineering institute "Nikola Tesla", 2016)
Determining high frequency electromagnetic field levels in urban areas represents a very complex task, having in mind the exponential growth of the number of sources embodied in public cellular telephony systems in the past twenty years. The main goal of this paper is a representation of a practical solution in the evaluation of measurement uncertainty for in-situ measurements in the case of spatial averaging. An example of the estimation of the uncertainty for electric field strength broadband measurements in the frequency range from 3 MHz to 18 GHz is presented.